Multi-Target Synergy Against Acute Lung Injury: Systems Pharmacology Decoding Dahuang-Huangqin Herb Pair’s Therapeutic Mechanism - Zhang J; Zhu X; Chen X; Liu H; Yan Z; Chen Z; Li Q; Yu W (Journal of Inflammation Research, 2025)
Jinquan Zhang,1– 4 Xuejiao Zhu,5 Xiaona Chen,2 Haichao Liu,1 Zhengzheng Yan,6 Zhixia Chen,2 Quan Li,1,2,4 Weifeng Yu3 1Guangzhou University of Chinese Medicine, Guangzhou, 510006, People’s Republic of China; 2Department of Anesthesiology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital & Shenzhen Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Shenzhen, 518116, People’s Republic of China; 3Department of Anesthesiology, Renji Hospital, Shanghai Jiao Tong University School of Medicine, Key Laboratory of Anesthesiology (Shanghai Jiao Tong University), Ministry of Education, Shanghai, People’s Republic of China; 4Shenzhen Clinical Medical College, Guangzhou University of Chinese Medicine, Shenzhen, 518100, People’s Republic of China; 5Department of Anesthesiology, The Second Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215004, People’s Republic of China; 6Department of Anesthesiology, Dongguan Key Laboratory of Anesthesia and Organ Protection, the Tenth Affiliated Hospital of Southern Medical University, Dongguan, Guangdong, People’s Republic of ChinaCorrespondence: Zhixia Chen, Email chenzhixia2007@163.com Quan Li, Email quanligene@126.comAim: This study investigates the therapeutic mechanisms of Radix et Rhizoma Rhei-Scutellaria baicalensis Georgi (DH-HQ) herb pair against acute lung injury (ALI) using integrative network pharmacology and multi-omics approaches.Methods: We combined bioactive compound screening of DH-HQ with ALI-related transcriptomics to construct dual interaction networks (herb-compound-target and protein-protein interactions). Core pathways were identified via bioinformatic analyses (GO/KEGG/GSEA) and validated through Mendelian randomization (to confirm gene causality), single-cell RNA sequencing (cell-type specificity), molecular docking (binding stability assessment), and in vivo ALI models (pathological/clinical validation).Results: Our analysis identified 207 active DH-HQ components and 93 therapeutic targets associated with ALI. PPI network analysis revealed five key regulatory targets: GAPDH, IL1B, IL10, MMP9, and TP53. Functional enrichment analyses demonstrated DH-HQ’s modulation of critical pathways including HIF-1 signaling and cytokine-cytokine receptor interaction. Molecular docking revealed strong compound-target binding affinities (energies: − 8.8 to − 7.3 kcal/mol), with emodin and baicalin showing the highest stability. In vivo, DH-HQ co-treatment significantly attenuated LPS-induced ALI, evidenced by reduced clinical scores and body weight recovery (p< 0.05). Multi-modal validation prioritized LTB4R/MMP9/POLR1B as diagnostic hubs (AUC > 0.70).Conclusion: This study elucidates DH-HQ’s multi-target mechanism in mitigating ALI via synergistic bioactive components (emodin and baicalin) and key pathway modulation. Preclinical evidence confirms efficacy through diagnostic hub genes and compound interactions, yet clinical application demands pharmacodynamic refinement.Keywords: acute lung injury (ALI), radix et Rhizoma Rhei (DaHuang), Scutellaria baicalensis Georgi (HuangQin), network pharmacology, single-cell sequencing, Mendelian randomization